ELEKTRONIK LEMBAR KERJA PESERTA DIDIK (E-LKPD) BERBASIS DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS - Caesavitri, Adelia; Marsitin, Retno; Yuwono, Timbul (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
Discovery learning is a learning model that is useful for developing students' mathematical reasoning skills. This research aims to develop E-LKPD based on discovery learning that are valid, practical, and effective. This research uses the ADDIE approach (Analysis, Design, Development, Implementation, and Evaluation). Product testing carried out included limited field trials to 10 students and extensive field trials to 24 students of SMP Negeri 1 Gondanglegi, Malang Regency. Data collection techniques utilize expert validation sheets, E-LKPD practicality questionnaires, and mathematical reasoning test sheets. The product validity tests conducted by experts (material, learning, and media experts) are declared valid with a score of 3.44. The product practicality test's results based on student responses obtained a score of 3.42 so it’s declared practical. The product effectiveness test's results obtained a completeness percentage of 70.8% and declared effective in learning activities. Students' reasoning ability is said to improve based on their test results. This study concludes that the E-LKPD based on Discovery Learning is valid, practical, and effective and can improve the students’ mathematical reasoning ability. It’s hoped that the E-LKPD developed used as mathematics teaching materials.